Novel ATXN1/ATXN1L::NUTM2A fusions identified in aggressive infant sarcomas with gene expression and methylation patterns similar to CIC-rearranged sarcoma - Feng Xu; Angela N. Viaene; Jenny Ruiz; Jeffrey Schubert; Jinhua Wu; Jiani Chen; Kajia Cao; Weixuan Fu; Rochelle Bagatell; Zhiqian Fan; Ariel Long; Luca Pagliaroli; et al. (Acta Neuropathologica Communications, 2022)
Abstract CIC-rearranged sarcomas are newly defined undifferentiated soft tissue tumors with CIC-associated fusions, and dismal prognosis. CIC fusions activate PEA3 family genes, ETV1/4/5, leading to tumorigenesis and progression. We report two high-grade CNS sarcomas of unclear histological diagnosis and one disseminated tumor of unknown origin with novel fusions and similar gene-expression/methylation patterns without CIC rearrangement. All three patients were infants with aggressive diseases, and two experienced rapid disease deterioration and death. Whole-transcriptome sequencing identified an ATXN1-NUTM2A fusion in the two CNS tumors and an ATXN1L-NUTM2A fusion in case 3. ETV1/4/5 and WT1 overexpression were observed in all three cases. Methylation analyses predicted CIC-rearranged sarcoma for all cases. Retrospective IHC staining on case 2 demonstrated ETV4 and WT1 overexpression. ATXN1 and ATXN1L interact with CIC forming a transcription repressor complex. We propose that ATXN1/ATXN1L-associated fusions disrupt their interaction with CIC and decrease the transcription repressor complex, leading to downstream PEA3 family gene overexpression. These three cases with novel ATXN1/ATXN1L-associated fusions and features of CIC-rearranged sarcomas may further expand the scope of “CIC-rearranged” sarcomas to include non-CIC rearrangements. Additional cases are needed to demonstrate if ATXN1/ATXN1L-NUTM2A fusions are associated with younger age and more aggressive diseases.